The Ecosystem Services of Marine Aquaculture: Valuing Benefits to People and Nature. (5th December 2018) - Alleway, Heidi K; Gillies, Chris L; Bishop, Melanie J; Gentry, Rebecca R; Theuerkauf, Seth J; Jones, Robert
Abstract: As the world's population continues to grow, the way in which ocean industries interact with ecosystems will be key to supporting the longevity of food and social securities. Aquaculture is crucial to the future supply of seafood, but challenges associated with negative impacts could impede increased production, especially production that is efficient and safe for the environment. Using the typology established by The Economics of Ecosystems and Biodiversity Initiative, we describe how marine aquaculture could be influential in supporting ecosystem services beyond solely the production of goods, through provisioning services, regulating services, habitat or supporting services, and cultural services. The provision of these services will vary, depending on functional traits of culture species, biotic and abiotic characteristics of the surrounding environment, farm design, and operational standards. Increasing recognition, understanding, and accounting of ecosystem service provision by mariculture through innovative policies, financing, and certification schemes may incentivize active delivery of benefits and may enable effects at a greater scale.